Social Relationships Among Sociology Students at the Faculty of Social and Political Sciences, Universitas Riau: A Sociometric Study - Inayah, Husnul; Hidir, Achmad; Rosaliza, Mita (Journal of Authentic Research, 2026)
This study analyzes the formation of student identity through a sociometric analysis within the Faculty of Social and Political Sciences at the Universitas Riau. The research is motivated by the high level of heterogeneity among students, who come from diverse cultural, regional, religious, and social backgrounds, resulting in a wide variety of social relationship patterns. The objective of the study is to identify the structure of social relationship networks, the position of individuals within the group, and the factors influencing the formation of student identity. The research method employs a quantitative approach using sociometric techniques. The population consists of 150 Sociology students from the Class of 2024, with a sample of 126 respondents obtained through voluntary sampling. Data were collected using a sociometric questionnaire and analyzed through the calculation of the choice status index, the rejection status index, the combined Index (CRS), and the visualization of sociograms. The results of the study indicate that the students' social relationship network is evenly distributed and inclusive, with no individuals completely isolated. Two popular individuals (stars) were identified with codes 91 (CRS=0.05) and 47 (CRS=0.03). There were 31 mutual pairs and several stable small groups (cliques). The primary factors in relationship formation were shared social identities and psychosocial conditions. The research results can be used as a basis for designing student development programs, such as orientation activities, cross-interest study groups, or mentoring programs, to facilitate the formation of a more equitable social network and reduce the potential for relational gaps among students.